Analytical reading on the dimensions of the phenomenon of illegal immigration - BOURENNI, NASSIM; AZOUZ, NOUREDDINE (Social Empowerment Journal, 2020)
The issue of clandestine migration has preoccupied many specialists and researchers in the social sciences for the reason that migration is one of the fundamental variables in the increase or decrease in population, beside its great importance and negative impact especially on the recipient countries, For this purpose, this intervention came to clarify the concept of clandestine immigration and its relationship to the concept of migration in general and to clarify also the meaning of the immigrant, and the most important scientific theories that tried to cover an analysis and objective explanation of this phenomenon.